Motivasi Etos Kerja Sebagai Implementasi Nilai-Nilai Ajaran Karma Marga di Desa Wisata Panglipuran, Kabupaten Bangli - Ida Ayu Dwidyaniti Wira; IGAP Novita Sari Paragae (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
A work ethic that is rooted or based on a work culture is a characteristic spirit that is typical of a person or group of people / society about work which is oriented towards an effort to always seek improvements or improvements to what has been achieved, by applying values, theories and methods new for the advancement of mankind. Work ethic and work essence according to Bhagawadgita that work is a yadnya. If the work ethic says work based on culture, then work in Catur Marga, especially Karma Marga, is work that is reflected in its yad form. Catur Marga which consists of bhakti marga, jnana marga, karma marga and king marga, the four of which are a system, namely a system or approach to connecting oneself with God Almighty. This is necessary in the sense that religion is inseparable from our belief and relationship as humans to God as the creator of the universe. This study aims to determine the form of motivation for the work ethic of Hindus in Panglipuran Tourism Village, Bangli Regency, work ethic motivation as the implementation of the values of karma marga teachings, and work ethics based on the values of karma marga teachings in the lives of Hindus in Panglipuran Tourism Village, Bangli Regency. In this study, using three theories, namely the theory of motivation, theory of values and social theory. This research uses methods, namely; method of determining the location, type of data and research data sources, research objects and subjects, data collection techniques, methods of determining informants, and methods of data analysis. In data collection techniques, the authors use methods, namely: observation, literature and interviews.Keywords: Work ethic, implementation, Karma marga teachings, Panglipuran Tourism Village